2019
DOI: 10.1097/sla.0000000000002829
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Resections Improve Survival Following Lung Metastasectomy of Colorectal Cancer Harboring KRAS Mutations

Abstract: AR seems to improve both the OS and TTPR in LM of CRC harboring KRAS mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Patients with wild‐type tumors had a similar risk of recurrence irrespective of the surgical technique. Similarly, Renaud et al found that KRAS patients who underwent lung metastasectomy had a lower risk of pulmonary recurrence and longer survival. Patients with wild‐type tumors had a similar risk of recurrence irrespective of the surgical technique (anatomical vs nonanatomical).…”
Section: Resultsmentioning
confidence: 91%
“…Patients with wild‐type tumors had a similar risk of recurrence irrespective of the surgical technique. Similarly, Renaud et al found that KRAS patients who underwent lung metastasectomy had a lower risk of pulmonary recurrence and longer survival. Patients with wild‐type tumors had a similar risk of recurrence irrespective of the surgical technique (anatomical vs nonanatomical).…”
Section: Resultsmentioning
confidence: 91%
“…The histology and genotype of the primary tumor are among the most important factors in prognosis and survival after PM. The mechanism of metastasis varies depending on the histological type of the tumor: colorectal metastases have a high rate of pleural invasion, and of interstitial and aerogenous spread of floating cancer cells, which are in turn associated with a high rate of local recurrence [24]. Melanoma does not show pleural invasion, but is associated with a higher probability of perivascular growth and an increased incidence of lymphangitic spread [25].…”
Section: Discussionmentioning
confidence: 99%
“…(95%CI:55%-58% , I 2 :97.6) for WT and mKRAS groups respectively. The overall prevalence of thoracic metastases based on four articles (24,25,27,28) was 20%(95%CI:16%-24% , I 2 :80.7) and 22%…”
Section: Sub-group Analysismentioning
confidence: 99%